Camps, Carcerality, and Late Victorian Empire: In Conversation with Aidan Forth’s Barbed-Wire Imperialism - Walker, Barrington (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2021)
This paper is a brief critical review essay of Aidan Forth’s recent award-winning work Barbed Wire Imperialism, winner of the 2019 Ferguson Prize of the Canadian Historical Association. The essay suggests a few potential slightly different emphases, trajectories, interpretive lenses and, perhaps, possibilities. Included among these are the centrality of the slave ship and transatlantic slavery for thinking about the roots of carcerality in the British Empire.